Text detector - Ibrahim, Rahinah (Universiti Putra Malaysia Press, 2016)
The brain gets very confused when it is bombarded with too much information. When Supervisors instruct novice researchers to search for inquiries that would lead them to new knowledge discoveries, it is the beginning of a never-ending journey if no true map is found in time! The practice of colour coding the constituents of the main research inquiries has led to a systemic documentation approach in the development of high impact innovative research proposals.